Timely introduction of AI teaching practices: an auxiliary tool for Chinese proposal writing - Tsui-Feng Huang; Sheng-Chieh Chou (International Journal of Evaluation and Research in Education (IJERE), 2026)
The rapid adoption of artificial intelligence (AI) is reshaping Chinese writing instruction in higher education, posing the risk of over-reliance on AI-generated text and exposure to biased content. To address these issues, this study applied scaffolding learning theory to design a writing instructional approach. This approach first uses scaffolding instruction to develop students’ foundational skills and then integrates iterative proposal writing with human-computer interaction using ChatGPT. Over a semester, more than 100 undergraduate students from three departments participated in a university writing course focused on event proposals. Students first wrote their own drafts, which were then refined through AI-assisted optimization. Two versions of the teacher evaluations were analyzed using statistical package for the social sciences (SPSS). A valid sample of 139 students revealed that novice writers benefited most from structured support, achieving above-average writing proficiency. Later, in-depth ChatGPT interaction led to higher-level content acquisition. This study confirms that combining scaffolding with guided AI can improve learning outcomes. This integrated scaffolding and AI instructional approach can foster independent writing skills and reduce inappropriate reliance on AI.